Методы и модели использования экспертно-аналитического знания для поддержки принятия решений в организации. Часть 1. Модели знания о решениях - Ильина, Е.П. (Проблеми програмування, 2016)
В работе представлен аппарат моделей корпоративного знания организации для экспертно-аналитической поддержки принятия ее решений. Формализован концепт Организационное решение с учетом всех стадий жизненного цикла последнего: от постановки проблемы до анализа результатов. Описаны модели категорий концептов из состава онтологии поддержки принятия решений и модель поля решений организации. Система отношений между концептами онтологии составляет предмет рассмотрения следующей части статьи, наряду с формализмом гармонизации поля решений. В роботі надано апарат моделей корпоративного знання організації для експертно-аналітичної підтримки прийняття її рішень. Формалізовано концепт Організаційне рішення з урахуванням усіх стадій життєвого циклу останнього від постановки проблеми до аналізу результатів. Описано моделі категорій концептів зі складу онтології підтримки прийняття рішень та модель поля рішень організації. Систем відношень між концептами онтології становить предмет розгляду наступної частини статті, як і формалізм гармонізації рішень. The paper is devoted to the formal representation of the organization decision by providing of the special kind of the organization knowledge models. Being employed in the organization information system these models give an ability for reusing of organization experience. Moreover they help to support analytical operations for quality management of organization decisions and decision making processes. The main components of the proposed knowledge models system are the Ontological Model for Decisions Support and the Decision Field of Organization. First of them includes such the categories of concepts as Gall, Gall Tree, Operation, Problem Situation, Side Influence, Decision, Package of Decisions, Value, Value tree. Their models are represented as the systems of the partial definitions for the concept that belong to the certain category and the set of rules for interpretation of each role position in such partial definition. Incomplete conceptual knowledge may be also represented in these models. Models proposed may be used for representation of the Organization Decisions Field and for constructing the mechanism of its analysis that is a subject of the next part of this article.